Hesperidin, Hesperetin, Rutinose, and Rhamnose Act as Skin Anti-Aging Agents - Novotná, Renáta; Škařupová, Denisa; Hanyk, Jiří; Ulrichová, Jitka; Křen, Vladimír; Bojarová, Pavla; Brodsky, Katerina; Vostálová, Jitka; Franková, Jana (Molecules (Basel, Switzerland), 2023)
Aging is a complex physiological process that can be accelerated by chemical (high blood glucose levels) or physical (solar exposure) factors. It is accompanied by the accumulation of altered molecules in the human body. The accumulation of oxidatively modified and glycated proteins is associated with inflammation and the progression of chronic diseases (aging). The use of antiglycating agents is one of the recent approaches in the preventive strategy of aging and natural compounds seem to be promising candidates. Our study focused on the anti-aging effect of the flavonoid hesperetin, its glycoside hesperidin and its carbohydrate moieties rutinose and rhamnose on young and physiologically aged normal human dermal fibroblasts (NHDFs). The anti-aging activity of the test compounds was evaluated by measuring matrix metalloproteinases (MMPs) and inflammatory interleukins by ELISA. The modulation of elastase, hyaluronidase, and collagenase activity by the tested substances was evaluated spectrophotometrically by tube tests. Rutinose and rhamnose inhibited the activity of pure elastase, hyaluronidase, and collagenase. Hesperidin and hesperetin inhibited elastase and hyaluronidase activity. In skin aging models, MMP-1 and MMP-2 levels were reduced after application of all tested substances. Collagen I production was increased after the application of rhamnose and rutinose.
Keywords: skin aging; rhamnose; Hesperidin; Skin Aging; Pancreatic Elastase; Humans; hesperidin; hyaluronoglukosaminidasa; lidé; Collagenases; rhamnosa; hesperetin; Rhamnose; normal human dermal fibroblast; kolagenasy; stárnutí kůže; Hyaluronoglucosaminidase; pankreatická elastasa; rutinose